496 RARE CASE OF WHIPPLE'S DISEASE COMPLICATED BY HEART FAILURE. Issue 1 (1st January 2007) - Dave, B.; Godkar, D.; Niranjan, S.; Lin, K.
Abstract : Introduction: Whipple's disease is a rare disorder caused by infection with Tropherna whipleii . We describe a patient who developed classic symptoms and eventual heart failure because of Whipple's disease. Case Report: Over a period of 5 years, a 45-year-old female developed frequent loose bowel movements, polyarthralgia, weight loss, edema, and, finally, dyspnea. On examination, she was thin and appeared ill, with jugular venous distention, a third heart sound, and edema. Echocardiography revealed normal left ventricular systolic function, mild right ventricular enlargement, abnormal diastolic septal motion, and a thickened pericardium. Cardiac catheterization revealed normal cardiac output and coronary arteries. A small bowel biopsy revealed macrophages in the lamina propria of the duodenum that were positive on periodic acid-Schiff staining, diagnostic of Whipple's disease. The patient began taking double-strength trimethoprim-sulfamethoxazole twice daily. Within 6 months, symptoms improved significantly. The patient showed improvement in both gastrointestial and cardiac symptoms. Repeat echocardiography done 1 year later showed a significant improvement in the ventricular sizes and function. The patient subsequently moved back to her home country and was lost to follow-up. Discussion: Cardiac involvement in Whipple's disease is rare. In fact, due to the nature of the disease, even extensive cardiac involvement may not be readily apparent. Endocarditis and polyserositis are the most conspicuous features. Pericarditis is seen in 60% of those with cardiac involvement but is rarely diagnosed during life. Myocardial involvement is rarer and can present as new-onset heart failure or sudden death. No clear relationship has been established between the extent of cardiac involvement and the severity of the disease. Although gastrointestinal symptoms are frequent, rarely, cardiac involvement may be the initial presentation. Unfortunately, Whipple's cardiac disease is frequently diagnosed postmortem. Since cardiac involvement can be fatal, there should be a high index of suspicion for cardiac infection in patients with Whipple's disease to ensure early recognition and treatment with antibiotics. The optimal duration of treatment for cardiac Whipple's disease is not known, so, currently, the same guidelines that apply to gastrointestinal disease are being applied to treat cardiac Whipple's disease as well.